Comprehensive analysis of the role of NLRC5 in gastrointestinal cancer: a systematic review - Rahadiani, Nur; Ghozali, Mohammad; Dewi, Dyah Laksmi (Universa Medicina, 2024)
BackgroundGastrointestinal (GI) cancer is affecting millions of people globally, leading to high incidence and mortality rates and a heavy economic burden. Nucleotide-binding oligomerization domain (NOD)-like receptors (NLRs) are a family of cytosolic pattern recognition receptors that regulate host defense responses against microorganisms. Among these, NLR family CARD domain-containing 5 (NLRC5) is assumed to function as a regulator of proinflammatory responses to intracellular pathogens. NLRC5 has been known to regulate immune responses, although its association with cancer remains controversial. This systematic review aimed to explore the roles and functions of NLRC5 in GI cancers. MethodsThree electronic databases, PubMed, Scopus, and ProQuest, were used for literature searching on March 18, 2024. From 921 articles found, 157 duplicates were removed, 671 were excluded based on title and abstract screening, and 84 were excluded based on full-text assessment, resulting in 19 articles included in this review. ResultsElevated NLRC5 levels have been observed in tumor tissues compared to normal tissues across esophageal, gastric, colorectal, and liver cancers. NLRC5 is also associated with increased tumor cell proliferation, migration, and invasion. Cancer cell sensitivity to 5-fluorouracil chemotherapy was found to be negatively correlated with NLRC5 expression. NLRC5 expression levels and genetic variations were also associated with cancer susceptibility to chemotherapeutic drugs and cancer survival. ConclusionNLRC5 potentially exhibits diverse functions in GI cancers, acting as a biomarker for diagnosis, disease progression, prognostic assessment, and determining therapeutic implications. Further investigations are warranted to explore these mechanisms and their potentials for the development of effective treatment of GI cancers.